ANALISIS STILISTIKA PADA NOVEL KAZE NO UTA O KIKE KARYA HARUKI MURAKAMI - Nur Izzati; Nana Rahayu; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses the stylistics analysis on novel Kaze no uta o kike by Haruki Murakami. The purpose of this study was to knowing the figures of speech especially simile in this novel, to knowing lexical meaning and stylistics meaning. The object of research is figures in the novel Kaze no uta o kike was written Haruki Murakami. This study is qualitative descriptive by interpreting the object under study based on the theory of stylistics meaning proposed by Djajasudarma (2013). Data obtained by noted the figures simile sentence in the novel, to analyze it was in terms of the lexical meaning and stylistics meaning. From the result of research, in the novel Kaze no uta o kike there are 11 sentence that show figure of speech simile. Stylistics meaning contained in this simile figure of speech, tells about the social conditions that occurred around 1970 in Japan. At that time, Japan was getting a great influence on the American. Both in terms of industry, economy, patterns of life, or habits in daily life.Key Word: Stylistics, simile